The Role of Ticagrelor in STEMI Fibrinolytic and Its Rationale to Utilize for Indonesian Patients - Daniel Tobing; Dafsah Juzar; Achmad Fauzi Yahya; Antonia Anna Lukito; Doni Firman; Sodiqur Rifqi; Abdul Hakim Alkatiri; Rurus Suryawan (Jurnal Kardiologi Indonesia, 2019)
Worldwide, ischemic heart disease is the most common cause of death and its frequency is increasing. ST-segment elevation myocardial infarction or STEMIis as form of ischemic heart disease with the highest mortality rate. Based on ESC (European Society of Cardiology) guideline 2017 for STEMI management, reperfusion therapywhich is primary PCI strategy is recommended over fibrinolysis within induced timeframes, but if timely primary PCI cannot be performed after STEMI diagnosis, fibrinolytic therapy is recommended within 12 hours of symptom onset in patients without contraindications. In fibrinolytic therapy, oral aspirin should be given, and Clopidogrel is indicated as an addition to aspirin. Although Clopidogrel is a recommended P2Y12receptor inhibitorin fibrinolytic therapy,PERKI guideline 2018 in ACS management also mention thatswitching to Ticagrelor can be considered in patients whowillundergo PCI treatmentafter fibrinolytic. In PLATO study, patients who have acute coronary syndrome with or without ST-segment elevation, treatment with ticagrelor as compared with clopidogrel significantly reduced the rate of death from vascular causes, myocardial infarction, or stroke. However, patients who received fibrinolytic therapy within 24 hours before randomization were excluded. WhileinSET-FAST study, Ticagrelor provides more prompt and potent platelet inhibition compared with Clopidogrel in patients undergoing PCI within 24 hours of receiving fibrinolysis for STEMI. TREAT study was conducted to evaluate the safety of ticagrelor in STEMI patients receiving fibrinolytic therapy within 24 hours.TREAT study concluded, at 30 days observation, in patients younger than 75 years with STEMI, delayed administration of Ticagrelor after fibrinolytic therapy was noninferior to Clopidogrel for TIMI major bleeding. Based on the result from PLATO study and preliminary TREAT study result on 30 days, the use of Ticagrelor within 24 hours after fibrinolytic therapy can be considered with comparable safety profile to Clopidogrel. Keywords: STEMI, fibrinolysis, ticagrelor